The Effect of Talkback Application on the Ability to Understand the Alphabet in Blind Peaple - Sulastri, Sulastri; Prystiananta, Nostalgianti Citra; Udhiyanasari, Khusna Yulinda (Linguistic, English Education and Art (LEEA) Journal, 2024)
This study discusses the effect of the talkback alphabet recognition application which is expected to help the blind people. This study aims to improve the ability to understand the alphabet through the talkback application for the blind people on Jl. Ahmad Yani Number 25, Tamansari Village, Bondowoso Regency. This type of research is Single Subject Research (SSR). This study uses an A-B design. The subject of this study is a blind person with the initials M. In the research process, two phases were used, namely the baseline phase and the intervention phase. In the baseline phase which was carried out for 5 sessions and 10 sessions in the intervention phase with a time of 40 minutes each session. From the results of the baseline percentage, namely 40%, 40%, 50%, 60% and 50%, the results obtained were continued with analysis in conditions and between conditions. The percentage of overlap obtained was 0% which shows that the intervention given to the blind person has an effect on the understanding of the alphabet in the talkback application. Thus, the formulation of the problem presented is answered that the talkback application is effective in improving the ability to understand the alphabet in blind people on Jl. Ahmad Yani Number 25, Tamansari Village, Bondowoso Regency. Keywords: Blind; Talkback application; Single Subject Research (SSR); alphabet letters